A novel stair‐finger grid type transistor for high‐performance millimeter‐wave power amplifier. Issue 10 (9th July 2022) - Li, Linhong; Zhang, Zhaofeng
Abstract: A novel stair‐finger grid type (SFGT) transistor layout is proposed in this letter to improve the f T f_T and f max f_ of large‐sized transistors for the millimeter‐wave power amplifier (PA). It combines the promoted stair‐finger transistor cells in a grid pattern to minimize parasitic capacitances and metal losses, which has been verified to provide higher gain over broadband by measurements. Two three‐stage dual‐differential PAs with different transistor layouts are compared in this letter. The PA employs a capacitive neutralization technique and distributed active transformer‐based combiner and divider. Fabricated in the Huali Microelectronics Corporation (HLMC) 40‐nm Complementary Metal Oxide (CMOS) (Co process, the PA with SFGT transistor [PA2] achieves higher gain and output power than the PA with the currently best‐known transistor [PA1]). PA2 achieves 15.22 dBm saturated output power ( P sat P_sat ), 14.25 dBm output power at 1 dB compression point ( P 1 dB P_1x0200AdB ), and 18.09 dB power gain when the basic supply is 1.1 V at 83 GHz.